Hybrid membrane to remove impurities in waste water - Noor Asyikin, Ahmad Shuhaimi (2010)
Hybrid membrane is for remove all contaminated inside the waste water. Nowadays, water pollution is becoming dangerous and sometimes not safe to use. The waste water actually comprise from liquid waste discharged by domestic residences, commercial properties, industry and agriculture. Main components of oil and gas industries waste water are acid gases, grease and lead. The research for waste water treatment has conducted by using hybrid membrane process. This method can remove the contaminants inside waste water and lowering the percentage of Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), pH, Turbidity and also carbon dioxide inside the waste water. This process is used sand silica column, activated carbon column and membrane column. The percentage removal based on amount of BOD, COD, pH and Turbidity of waste water before and after for each column. The purpose of this study is not only to remove carbon dioxide in waste water but also to remove all the contaminated inside the waste water. The difference compositions of membrane give difference percentage of removal. The additives are added about 1wt%, 3%wt and 5%wt of Monosodium Glutamate (MSG) to investigate the effect of MSG to the membrane performance. The overall process was started at first column which is sand silica column, then activated carbon column and the last is membrane column. The process gives lower amount of BOD, COD, pH and Turbidity. From the result shows that MSG based membrane with 3wt% MSG, achieve the best clearance about 80%.